Analisis Manhaj Khusus Dalam Tafsir Mafâtih Al-Ghaib Karya Al-Razi - Tatan Setiawan; Muhammad Panji Romdoni (Jurnal Iman dan Spiritualitas, 2022)
This article discusses the special manhaj in al-Razi's interpretation of Mafâtih al-Ghaib. This study is discussed to find out the methodology that is specifically carried out by al-Razi in his research. The writing of this article uses a literature-based descriptive-analytical method. This study concludes that there are 11 special manhajs used by al-Razy in Mafatih al-Ghayb. First, the writer is familiar with mas'alah, bahts, qaul, and ihtimal. Second, using imaginary dialogue to eliminate misunderstandings or sharpen the discussion. Third, using ash'ariyyah theology in theological verses and Shafi'i fiqh in legal verses. Fourth, strengthen the interpretation with various opinions of scholars. Fifth, put qira'at mutawatir in verse and reject it if it is contradictory. Sometimes hujjah with qira'at put forward by grammar experts, even accept qira'at if appropriate and strengthen it against a verse. Sixth, using the munasabah theory. Seventh, using asbab al-nuzul. Eighth, using nasakh-mansukh in the sense of al-raf'. Ninth, the hadith used is limited in fiqh matters. Tenth, using 'Arabic poetry. Eleventh, using Israel's history objectively.